هياكل الصكوك الهجينة : دراسة فقهية تأصيلية تحليلية - مختار، أحمد محمد (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
This study aims to analyze one of the common sukuk structures that has gained popularity and has been extensively applied for investment and asset management in the last decade in all main Sukuk markets. This structure – Hybrid Sukuk- is characterized by an interesting feature i.e. combining different contracts and mixing different assets in one issuance. This feature was designed to achieve two purposes – flexibility in asset selection and the permissibility of trading in secondary market. Nonetheless، these objectives are not achieved without encountering Shari'ah issues. Some of which are peculiar to this structure and some are common in all structures. Applying qualitative methods، this study، after setting the appropriate theoretical framework ، has descriptively analyzed three main types of hybrid sukuk with examples of current issuances. The researcher then studied some of the Shari'ah issues in these sukuk including the combination of contract and mixing of assets and other issues that are common in all sukuk structures applying the Fiahi method of Tkhriiju Alfuru' 'Ala Alusul. The research found that combining Murabaha and Mudhraba is not permissible. This also applies to combining Murrabaha and Wakala bil istithmar because in both case combined contracts are different in nature and the combination in of itself leads to some violations of Sharia'ah principles. However، the combination of Wakalah bil khadamat and Wakalah bil istithmar is permissible as no Shari'ah issue was found to be arising from the combination in of itself. The study also compared AAOIFI Shari'ah standard 59 to applicable rules and regulations in capital market and found that the requirement of selling an entity for the mix of asset to be allowed is contradictory to the prevailing regulations. The researcher suggested the drafting new laws that acknowledge sukuk as a different class that is not appropriately regulated under the umbrella of stock nor bonds. These new laws should be coupled with accounting and auditing standards that would protect sukuk-holders' interest from agency problems arising from participation contracts used in sukuk